Two Oral Midazolam Preparations in Pediatric Dental Patients: A Prospective Randomised Clinical Trial - Katayoun Salem; Shaqayegh Kamranzadeh; Maryam Kousha; Shahnaz Shaeghi; Fatemeh AbdollahGorgi (Hindawi Limited, 2015)
Pharmacological sedation is an alternative behavior management strategy in pediatric dentistry. The aim of this study was to compare the behavioral and physiologic effects of "commercially midazolam syrup" versus "orally administered IV midazolam dosage form (extemporaneous midazolam (EF))" in uncooperative pediatric dental patients. Eighty-eight children between 4 to 7 years of age received 0.2-0.5 mg/kg midazolam in this parallel trial. Physiologic parameters were recorded at baseline and every 15 minutes. Behavior assessment was conducted objectively by Houpt scale throughout the sedation and North Carolina at baseline and during injection and cavity preparation. No significant difference in behavior was noted by Houpt or North Carolina scale. Acceptable behavior (excellent, very good, and good) was observed in 90.9% of syrup and 79.5% of EF subjects, respectively. Physiological parameters remained in normal range without significant difference between groups and no adverse effect was observed. It is concluded that EF midazolam preparation can be used as an acceptable alternative to midazolam syrup.